2016
DOI: 10.1590/s0034-759020160302
|View full text |Cite
|
Sign up to set email alerts
|

Improving Financial Inclusion: Towards a Critical Financial Education Framework

Abstract: Empirical research suggests that financial inclusion initiatives - such as facilitating access to financial resources or providing microcredit - are alone not enough to lower socioeconomic disparities. In this article, we adopt a critical stance as a guide for our empirical investigation. Our aim is to propose a financial education framework, tailored to low-income micro-entrepreneurs, that embraces new information and communication technologies (ICTs) and seeks to improve financial inclusion and social emanci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
21

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 27 publications
0
10
0
21
Order By: Relevance
“…Financial literacy is the foundation of financial inclusion (Atkinson & Messy, 2013;Birochi & Pozzebon, 2016). The previous study also found that higher financial literacy leads to greater financial well-being and less financial concerns (Taft, Hosein, & Mehrizi, 2013).…”
Section: Financial Literacymentioning
confidence: 88%
See 1 more Smart Citation
“…Financial literacy is the foundation of financial inclusion (Atkinson & Messy, 2013;Birochi & Pozzebon, 2016). The previous study also found that higher financial literacy leads to greater financial well-being and less financial concerns (Taft, Hosein, & Mehrizi, 2013).…”
Section: Financial Literacymentioning
confidence: 88%
“…According to the same report, Indonesia has the largest gap in active financial account holdings in which active account usage by those who live below the poverty line reached just 12% in 2015. Theoretically and empirically, financial literacy has become the stepping stone to financial inclusion (Atkinson & Messy, 2013;Birochi & Pozzebon, 2016). Therefore, the Indonesian government is currently contemplating important improvements in financial literacy in Indonesia and has made financial education and financial literacy a national campaign as the first pillar of the National Financial Master Plan in 2015-2019(Indonesian Financial Services, 2015.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, the collected data were interpreted, via content analysis, by means of comparison with the a priori categories of the 2iDf model constructs, as proposed by Birochi and Pozzebon (2016), the objective of same FIGURE 4 Data analysis. Source: Adapted from Freitas and Janissek (2000, p. 85) being to identify the impact of an ICT-equipped bank boat, named Agência Barco, in the financial inclusion of the riverine locations served.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, authors such as Dávila and Dávila [8] have suggested that research based on reflections can contribute to the understanding of those aspects that at first glance are not valued. Thus, it is necessary to review both the theoretical aspects of the topic when carrying out social research with a focus on issues such as education [9], while at the same time making contrasts to generate new knowledge or approaches to a problem of interest [10]. Once the previous concepts had been revised, the research stages were designed and illustrated in figure 1.…”
Section: Methodsmentioning
confidence: 99%